ANALISIS KEMAMPUAN LITERASI DAN NUMERASI SISWA SMPN 04 MERANGIN BERDASARKAN HASIL TRY OUT AKADEMIK: SEBUAH STUDI DIAGNOSTIK AKADEMIK - Yuliasary, Sisca; Hawari, Ken; Elfisa, Yesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates students’ reading literacy and numeracy at SMPN 04 Merangin using Academic Try Out results as a diagnostic basis to formulate data informed instructional follow-ups. Employing a qualitative case study design, the study primarily draws on document analysis of Try Out score reports and test blueprints/items, supported by domain/indicator coding and descriptive statistics to map achievement profiles. The participants were 16 students completing 40 items (20 literacy; 20 numeracy). Results indicate a mean literacy score of 61.25% (SD=16.68), a lower mean numeracy score of 49.38% (SD=15.69), and an overall mean of 55.31% (SD=15.62), with scores ranging from 32.5% to 82.5%. Ten out of sixteen students scored below 50% in numeracy, compared to five in literacy; seven students were below 50% overall. The literacy–numeracy gap was relatively consistent, averaging 11.88 percentage points, with several students showing gaps of ≥20 points highlighting numeracy as the primary intervention priority. These findings underscore the value of leveraging Try Out data as a needs-assessment map to guide targeted numeracy remediation emphasizing modeling and interpretation, strengthening higher-order reading literacy (inference and evaluation), and implementing indicator-based formative assessment to monitor progress over time.